EFEKTIVITAS CEC (CENDEKIA ENGLISH CLUB) DALAM MENINGKATKAN KEMAMPUAN BAHASA INGGRIS MAHASISWA JURUSAN AKUNTANSI STIE CENDEKIA BOJONEGORO - Hafidza Nash'ul Amrina (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2017)
The aim of this research is to find out the effectivenes of CEC (Cendekia English Club) Program in developing the students English ability in STIEKIA. This research is descriptive qualitative. Questionnaire, observation and students english score are used to get the data. The resulth of the research shows that 70% students said that CEC program is very usefull. 80 % students said that their ability in speaking is developed very well. 75% stated taht their speaking ability is developed very well. 90% of the students said that their reading abilty is also developed well and for writing ability they stated that 70% developed well. The result of the students english score shows that 90% of the students which follow the CEC program get A score, while only 15% of non CEC students get A score. Those result show that CEC program in STIEKIA is efective to develop students english ability.